Escherichia coli hemolysin is a potent inductor of phosphoinositide hydrolysis and related metabolic responses in human neutrophils. - Grimminger, F (1991)
Escherichia coli hemolysin (Hly) is a proteinaceous pore-forming exotoxin that probably represents a significant virulence factor in E. coli infections. We investigated its influence on human polymorphonuclear neutrophils (PMN), previously identified as highly susceptible targets. Hly provoked rapid secretion of elastase and myeloperoxidase, generation of superoxide, and synthesis of platelet-activating factor (PAF) and lyso-PAF. Concomitantly, marked phosphatidylinositol (PtdIns) hydrolysis with sequential appearance of the inositol-phosphates, inositol-phosphates, inositol triphosphate, diphosphate, and monophosphate, respectively, and formation of diacylglycerol, occurred. The metabolic responses displayed distinct bell-shaped dose dependencies, with maximum events noted at low toxin concentrations of 0.1-0.5 hemolytic units per milliliter. PtdIns hydrolysis and metabolic responses elicited by Hly exceeded those evoked by optimal concentrations of formylmethionyl-leucyl phenylalanine, PAF, leukotriene B4, A23187, or staphylococcal alpha-toxin. The toxin-induced effects were sensitive toward modulators of PMN stimulus transmission pathways (pertussis toxin, the kinase C inhibitor H7, and phorbol myristate acetate "priming"). We conclude that the marked capacity of low doses of Hly to elicit degranulation, respiratory burst, and lipid mediator generation in human PMN probably envolves signal transduction via PtdIns hydrolysis.